Clot Lysis and Antimitotic Study of Ficus glomerata Roxb Fruit Extracts. (31st March 2014) - Shivasharanappa, Kirankumar; Londonkar, Ramesh
Abstract : The present study was carried out to investigate the thrombolytic and antimitotic potentiality of various extracts of fruits of Ficus glomerata, a traditional medicinal plant, using an in vitro assay method. Three crude extracts such as petroleum ether (FGPE), chloroform (FGCE), and methanol (FGME) were used for the study, with a standard (streptokinase) and negative control (sterile distilled water) to validate the method. The thrombolytic nature of the plant was found significant with methanol extract and chloroform and petroleum ether extracts have recorded mild activity, when compared with the negative control (sterile distilled water). The extracts have shown mild clot lysis, that is, 2.16%, 23.06%, 27.60%, and 47.74% of sterile distilled water, FGPE, FGCE, and FGME, respectively, while the standard (streptokinase) has shown 74.22% clot lysis. FGME inhibited the root growth in number as well as length effectively, followed by FGPE, while FGCE exhibited moderate antimitotic activity and it was supported by mitotic index. Therefore, the obtained results suggest that among all the extracts of plant the methanolic extract has shown highest thrombolytic and antimitotic activity.